See many, do one, teach many more: Assessing quality and reliability of publicly available endoscopic videos in rhinology. Issue 12 (11th April 2022) - Bitner, Benjamin F.; Gowda, Sanjita; Mark, Michelle E.; Warner, Danielle C.; Tajudeen, Bobby A.; Kuan, Edward C.
Abstract: Objectives: The use of video recording is commonplace in rhinology given the increased use of endoscopes when evaluating patients in the office and the operating room and for its educational potential. This study aimed to determine the quality of publicly available endoscopic videos in rhinology. Methods: A video search was performed on YouTube in April 2020 and included all videos since its inception in 2005 using terms related to rhinology found in the Accreditation Council for Graduate Medical Education (ACGME) Case Log Coding Guide. Videos which met inclusion criteria were evaluated for video metrics and quality using validated scoring systems: Video Power Index (VPI), modified Journal of American Medical Association (JAMA) benchmark criteria, modified global quality score (GQS), and modified DISCERN criteria. Results: A total of 138 videos were evaluated, 114 of which were uploaded independently, and 24 videos were uploaded by an academic institution. Academic‐affiliated videos have higher like ratio at 91.7 ± 7.55% compared with 86.27 ± 17.44% ( p = 0.018). Academic‐affiliated videos have higher JAMA benchmark scores, DISCERN criteria scores, and GQS values (1.71 ± 0.55 vs. 1.66 ± 0.49 [ p = 0.66]), (3.33 ± 0.56 vs. 2.85 ± 0.65 [ p < 0.001]), (4.38 ± 0.81 vs. 3.43 ± 1.01 [ p < 0.001])], respectively. There was no significant difference in VPI ( p = 0.73). Conclusions: Endoscopic videos are rapidly growing in prominence and remain an important part of surgical education, but overall are heterogeneous in quality and reliability, necessitating an effort to establish both video sharing regulations and objective standards of quality.